Simultaneous Rates of Ribonucleic Acid and Deoxyribonucleic Acid Syntheses for Estimating Growth and Cell Division of Aquatic Microbial Communities - Karl, David M. (1981)
A method for measuring rates of ribonucleic acid (RNA) and deoxyribonucleic acid (DNA) syntheses using a single radioactive precursor has been devised and tested using bacterial cultures and natural assemblages of marine and freshwater microorganisms. The procedure is based upon the uptake and incorporation of exogenous [(3)H]adenine into cellular adenosine triphosphate and deoxyadenosine triphosphate pools which serve as the immediate precursors for the adenine incorporated into RNA and DNA, respectively. It is proposed that the DNA/RNA rate ratio is correlated with the specific growth rate of microorganisms and can be used as an index for estimating and comparing the productivities of microbial assemblages in nature. This technique can also be used to detect discontinuous growth and cell division processes which frequently occur in surface plankton populations. The DNA/RNA rate ratios measured in a variety of aquatic ecosystems ranged from 3.3 to 31.8% without significant correlation to total microbial biomass.